The twofold debris disk around HD 113766 A: warm and cold dust as seen with VLTI/MIDI and Herschel/PACS - Olofsson, Johan; Henning, Thomas; Nielbock, Markus; Augereau, J.-C.; Juhàsz, A.; Oliveira, I.; Absil, O.; Tamanai, Akemi (Astronomy and astrophysics, 2013)
Context: Warm debris disks are a sub-sample of the large population of debris disks, and display excess emission in the mid-infrared. Around solar-type stars, very few objects (~2% of all debris disks) show emission features in mid-IR spectroscopic observations that are attributed to small, warm silicate dust grains. The origin of this warm dust could be explained either by a recent catastrophic collision between several bodies or by transport from an outer belt similar to the Kuiper belt in the solar system. Aims: We present and analyze new far-IR Herschel/PACS photometric observations, supplemented by new and archival ground-based data in the mid-IR (VLTI/MIDI and VLT/VISIR), for one of these rare systems: the 10-16 Myr old debris disk around HD 113766 A. We improve an existing model to account for these new observations. Methods: We implemented the contribution of an outer planetesimal belt in the Debra code, and successfully used it to model the spectral energy distribution (SED) as well as complementary observations, notably MIDI data. We better constrain the spatial distribution of the dust and its composition. Results: We underline the limitations of SED modeling and the need for spatially resolved observations. We improve existing models and increase our understanding of the disk around HD 113766 A. We find that the system is best described by an inner disk located within the first AU, well constrained by the MIDI data, and an outer disk located between 9-13 AU. In the inner dust belt, our previous finding of Fe-rich crystalline olivine grains still holds. We do not observe time variability of the emission features over at least an eight-year time span in an environment subjected to strong radiation pressure. Conclusions: The time stability of the emission features indicates that μm-sized dust grains are constantly replenished from the same reservoir, with a possible depletion of sub- μm-sized grains. We suggest that the emission features may arise from multi-composition aggregates. We discuss possible scenarios concerning the origin of the warm dust observed around HD 113766 A. The compactness of the innermost regions as probed by the MIDI visibilities and the dust composition suggest that we are witnessing the results of (at least) one collision between partially differentiated bodies, in an environment possibly rendered unstable by terrestrial planetary formation.